Rising HIV prevalence among men who have sex with men in Nigeria: a trend analysis - George I.E Eluwa; Sylvia B. Adebajo; Titilope Eluwa; Obinna Ogbanufe; Oluwafunke Ilesanmi; Charles Nzelu (BMC, 2019)
Abstract Background Men who have sex with men (MSM) are conservatively estimated to be less than 1% of the Nigerian population yet nationally account for about 20% of new HIV infection. We estimated the trend in HIV prevalence and determined correlates of HIV infection among MSM. Methods This study used data from respondent-driven sampling in three rounds of integrated biological and behavioral surveillance survey (2007, 2010 and 2014) and covered three states in 2007, six states in 2010 and eight states in 2014. Each round used similar methodology and thus allows for comparison. Behavioral data were obtained using a structured pre-coded questionnaire. Differences in categorical variables were assessed with Chi Square. Logistic regression was used to identify factors associated with HIV. Results A total of 879, 1545 and 3611 MSM were recruited in 2007, 2010 and 2014 respectively. Median age was 22 years for 2007 and 2014 while it was 24 years in 2010. About one-third of MSM in 2007 and 2014 and about two-fifths in 2010 had engaged in transactional sex. HIV prevalence increased from 14% in 2007 to 17% in 2010 to 23% in 2014 (p < 0.0001). Factors associated with HIV include older age ≥ 25 years (adjusted odds ratio AOR:2.41; 95% CI:1.84-3.16); receptive anal sex (AOR:1.92; 95% CI:1.54-2.40) and history of sexually transmitted infections (AOR:1.26; 95% CI:1.02-1.55). Conclusion There's been a consistent and significant increase in HIV prevalence among MSM with about 10-percentage points relative increase per year over 7 years. Older MSM were more likely to be HIV positive and this may reflect their prolonged exposure to high risk sexual activities. Evidence based interventions are urgently needed to mitigate intra-group HIV transmission and propagation of HIV epidemic between MSM and the general population.